2020
DOI: 10.1016/j.psj.2019.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of short-term storage on the quantity of extended-spectrum beta-lactamase–producing Escherichia coli in broiler litter under practical conditions

Abstract: Applying broiler litter containing extended-spectrum beta-lactamase ( ESBL )–producing Escherichia coli ( E. coli ) to arable land poses a potential risk for humans to get colonized by contact with contaminated soil or vegetables. Therefore, an inactivation of these bacteria before land application of litter is crucial. We performed 2 short-term litter storage trials (one in summer and winter, respectively), each covering a time span of 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
1
25
1
1
Order By: Relevance
“…ESBL-producing E. coli are rapidly inactivated in chicken litter. In a study recently published by Siller et al (2020), ESBL-producing E. coli concentrations decreased from an average of 3.4 × 10 5 cfu g −1 in fresh chicken litter below the detection limit after storage periods of 36 h in the summer and 72 h in the winter. To limit this inactivation in the litter used in the wind tunnel trials, the timespan between litter collection and aerosolization was minimized.…”
Section: Discussionmentioning
confidence: 87%
“…ESBL-producing E. coli are rapidly inactivated in chicken litter. In a study recently published by Siller et al (2020), ESBL-producing E. coli concentrations decreased from an average of 3.4 × 10 5 cfu g −1 in fresh chicken litter below the detection limit after storage periods of 36 h in the summer and 72 h in the winter. To limit this inactivation in the litter used in the wind tunnel trials, the timespan between litter collection and aerosolization was minimized.…”
Section: Discussionmentioning
confidence: 87%
“… Gazal et al (2015) analyzed poultry litter after the composting process, observing that few isolates (6.3%) contained virulence genes from extra-intestinal pathogenic E. coli and were susceptible to a large number of antimicrobials. Siller et al (2020) demonstrated that short-term storage reduces the amount of ESBL-producing E. coli in poultry litter. Therefore, the practice of composting or storage is a good alternative for eliminating possible pathogens and multiresistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that chicken manure carried additional pathogens, including Enterococcus faecium and extended-spectrum beta-lactamase (ESBL) producing Escherichia coli (Thiel et al ., 2020). However, ESBL E. coli died off within a few days during manure storage (Siller et al ., 2020) and enterococci rapidly declined in soil within weeks after fertilization (Thiel et al ., 2020). In the present study, in contrast, we demonstrate that viable C. difficile remained detectable in fertilized soil for several years and hence represented a long-lasting pollution.…”
Section: Discussionmentioning
confidence: 99%